Cardio-thoracic ratio is stable, reproducible and has potential as a screening tool for HIV-1 related cardiac disorders in resource poor settings - Esmail,H; Oni,T; Thienemann,F; Omar-Davies,N; Wilkinson,RJ; Ntsekhe,M (PLOS One, 2016)
BackgroundCardiovascular disorders are common in HIV-1 infected persons in Africa and presentation is often insidious. Development of screening algorithms for cardiovascular disorders appropriate to a resource-constrained setting could facilitate timely referral. Cardiothoracic ratio (CTR) on chest radiograph (CXR) has been suggested as a potential screening tool but little is known about its reproducibility and stability. Our primary aim was to evaluate the stability and the inter-observer variability of CTR in HIV-1 infected outpatients. We further evaluated the prevalence of cardiomegaly (CTR≥0.5) and its relationship with other risk factors in this population.MethodologyHIV-1 infected participants were identified during screening for a tuberculosis vaccine trial in Khayelitsha, South Africa between August 2011 and April 2012. Participants had a digital posterior-anterior CXR performed as well as history, examination and baseline observations. CXRs were viewed using OsiriX software and CTR calculated using digital callipers.Results450 HIV-1-infected adults were evaluated, median age 34 years (IQR 30–40) with a CD4 count 566/mm3 (IQR 443–724), 70% on antiretroviral therapy (ART). The prevalence of cardiomegaly was 12.7% (95% C.I. 9.6%-15.8%). CTR was calculated by a 2nd reader for 113 participants, measurements were highly correlated r = 0.95 (95% C.I. 0.93–0.97) and agreement of cardiomegaly substantial κ = 0.78 (95% C.I 0.61–0.95). CXR were repeated in 51 participants at 4–12 weeks, CTR measurements between the 2 time points were highly correlated r = 0.77 (95% C.I 0.68–0.88) and agreement of cardiomegaly excellent κ = 0.92 (95% C.I. 0.77–1). Participants with cardiomegaly had a higher median BMI (31.3; IQR 27.4–37.4) versus 26.9; IQR 23.2–32.4); p<0.0001) and median systolic blood pressure (130; IQR 121–141 versus 125; IQR 117–135; p = 0.01).ConclusionCTR is a robust measurement